Slaughterhouse hygiene training in western Kenya improves practices and reduces contamination of tools and water but does not reduce contamination of meat - Cook, Elizabeth A.J.; Ambler, Kate; Hoffmann, Vivian; Otoigo, Lilian; Kiarie, Alice (International Livestock Research Institute, 2024)
Inadequate hygiene and sanitation facilities at slaughterhouses in Kenya have been shown to lead to contamination of meat and transmission of pathogens. Meat inspectors visit slaughter facilities daily; their duties could be expanded to include training workers on hygiene practices.